Analisis Kesulitan Belajar Mahasiswa Program Studi Pendidikan Matematika dalam Mempelajari Matematika Ekonomi - Utin Desy Susiaty; Muhamad Firdaus; Hodiyanto Hodiyanto (SAP (Susunan Artikel Pendidikan), 2017)
The aim of this research is to investigate students’ learning difficulties in mathematical economics in 2015/2016 academic year. This research is a descriptive qualitative research, the subjects of which are 3 students taking mathematical economics with low, average and high ability category. They are selected based on the recommendation from a mathematical economics lecturer. Data are collected using documentation and direct communication techniques, with data collection tools in the form of documentation of questions and results of Midterm (UTS) and Final Examinations (UAS) in mathematical economics and of interview guides. After collecting the data, the researchers analyze the results of the Examinations and of interview to investigate the students’ learning results to identify their learning difficulties in mathematical economics. The result of the research shows that students with high ability category (M1) do not have learning difficulties in learning mathematical economics; students with average ability category (M2) lack understanding of the exponent if the cardinal numbers are in fraction forms; students with low ability category (M3) do not have understanding of the concept of profit and loss, especially the one related to income and expenses, of the concept of the exponent so that they are wrong when determining the final results and of the meaning of the questions, especially if there is.